Mulching enhances aonla yield in rainfed areas - Singh, A K; Singh, Sanjay; Rao, V V Appa (Indian Horticulture, 2015)
Organic mulches improves the soil quality by enriching organic matter after decomposing, making the soil loose, improving the soil structure and root growth, reducing the compactness of soil and oxidation of organic carbon, increasing the infiltration rate of water and improving the water holding capacity of soil. Organic matter of the mulch is also a source of plant nutrients and creates an ideal environment for proper growth and development of flora and fauna of soil. Among various kinds of mulches, use of paddy straw mulches has shown favourable and encouraging results in terms of soil quality, soil microbial and earthworm population, growth and yield of aonla with quality fruits under dryland condition in Gujarat. Therefore, the same has been recommended to the farmers for its commercial exploitation which is being adopted by farmers growing orchard under rainfed conditions.